THE MICROBIAL GROWTH INHIBITION PROFILE OF SELECTED INDONESIAN SPICES ESSENTIAL OILS ON TOFU DURING 8-DAY STORAGE - Alwani Hamad; Asmiyenti Djalisrin Djali; Dianita Yulia Sukma Dewi; Eka Yuliani Saputri; Eli Nurlaeli; Intan Nur Fadlilah; Muliastri Mentari; Dwi Hartanti (Journal of Chemical Process and Material Technology, 2022)
This study evaluated the profile of microbial growth inhibition on tofu treated by the essential oil of the selected spices. The microbial growth on the tofu was visually observed by the pour plate method, while their number was enumerated by the indirect optical density (OD) method. All the tested essential oils were visually reduced the microbial growth on tofu during storage. Each spices oil showed a different inhibition pattern, with bay leaf, galangal, and ginger oils exerting favorable effects for the most prolonged period. The day-bay-day comparison demonstrated that the best inhibition effect was on day-6 and -8, with bay leaf and galangal oils showing the most promising activity. The best profile of both essential oils might play a vital role in the tofu preservation process by natural products.